Peningkatan Eksistensi Media Sosial Marketing dan E-Commerce terhadap Customer Retention Kahiji Coffee & Dinner - Stevie Pratama (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the impact of implementing social media marketing and e-commerce strategies on customer retention at Kahiji Coffee & Dinner in Bandung. Using a mixed quantitative and qualitative method, this research analyzes the effectiveness of digital marketing strategies in increasing engagement rates and retaining customers. The results show a significant increase in engagement rate, reaching 5.5% (exceeding the 2.3% target) and a customer retention rate of 69%. The implemented strategies include social media optimization, creative content creation, use of paid advertising, and e-commerce enhancement. This research provides valuable insights for SMEs in optimizing digital marketing strategies in the food and beverage industry.